ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MUSYARAKAH PADA BANK UMUM SYARIAH TAHUN 2017-2021 - Jannah, Taniantari Nur; Primitasari, Novi (Journal of Financial Economics & Investment, 2023)
This research was conducted to discover how influential Supreme Audit Institution (SAI), and Non Performing Financing (NPF) to profit sharing based Musyarakah Financing which collected from quarterly financial report Bank Umum Syariah. The researcher expects to make this research beneficial for the development of the Financial and Banking industry. The data used in this research is a secondary data which is an quarterly financial report Bank Umum Syariah published by Otoritas Jasa Keuangan from 2017-2021 Bank Umum Syariah population. This research uses Multiple Linear Regression analysis technique. After the researcher conducting the research, it found out that, SAI, NPF, also ROA doesn’t significant to the Musyarakah financing.